Universalism and Targeting: An International Comparison using the LIS database - Aya K. Abe (Luxembourg Income Study (LIS), 2001)
In combating poverty, whether or not to design a universal program or a targeted program has been a perpetual dilemma. The objective of this paper is to conduct an international comparison of the 'universality' and 'targeting' of social security systems. The paper presents an outline of methodologies used in assessing the universality and categorical targeting of the poor. Two methodologies are employed. The first builds on the work of Beckerman and examines how positive and negative net transfers are distributed using micro-data from eleven countries; the second employs a logistic regression method to estimate the effects of the initial poverty gap and categorical status of a household on its poverty outcome. The data used are drawn from the Luxembourg Income Study (LIS) database and a micro-data from the Ministry of Health, Labor and Welfare of Japan.
Keywords: 330; Soziale Sicherheit; Sozialpolitik; Zielgruppe; Welt